Znaczenie marketingu terytorialnego w kreowaniu wizerunku i marki jednostki samorządu terytorialnego na przykładzie województwa podkarpackiego - Gorączko, Joanna (Polityka i Społeczeństwo, 2021)
The article pertains to the issue of territorial marketing in creating the image of lo-cal government unit on the example of the Subcarpathian Voivodeship. The aim of this paper is to identify by which methods the region builds brand and positive perception. Analysis of the use of territorial marketing tools is conducted based on the method of research sources pertaining to the theme. It was proved that the Subcarpathian region concentrates on social capital and openness for innovations, but still needs a greater emphasis on marketing.